2011
DOI: 10.1167/iovs.10-5708
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Reveals Optic Tract Degeneration in Hemianopia

Abstract: Transsynaptic degeneration had already begun 18 months after lesion. Although there was no visible decrease in volume at this stage, the white matter integrity was compromised. Significant decrease in volume could be visualized at longer durations of hemianopia. This method of objectively assessing structural images provides an effective, noninvasive approach to monitor the timescale of optic tract degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 13 publications
2
70
0
Order By: Relevance
“…20,21 More recently, resource to high-resolution magnetic resonance imaging revealed optic tract thinning in hemianopic patients. 22 The development of OCT technology allowed for an easy and non-invasive analysis of the retina and the optic disc. RNFL analysis and more recently the study of RGC layers have been used as potential methods in TRD research.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 More recently, resource to high-resolution magnetic resonance imaging revealed optic tract thinning in hemianopic patients. 22 The development of OCT technology allowed for an easy and non-invasive analysis of the retina and the optic disc. RNFL analysis and more recently the study of RGC layers have been used as potential methods in TRD research.…”
Section: Discussionmentioning
confidence: 99%
“…A more speculative explanation is trans-synaptic retrograde degeneration, a phenomenon controversially discussed for decades [31][32][33][34][35][36][37][38][39][40], induced by optic radiation damage causing retinal thinning detectable by OCT. In our study, the association between focal tissue destruction in the OR and thinning of the RNFL remained significant even when considering exclusively patients without a history of ON, indicating that retinal axonal degeneration in MS occurs partially independent of ON -a notion also supported by previous OCT studies [14][15][16]41].…”
Section: Discussionmentioning
confidence: 99%
“…1 A recent study, however, suggested that retrograde transsynaptic degeneration in human optic tract is functionally apparent as early as 18 months after cortical damage. 30 Addi- tionally, a long delay of structurally visible changes compared with more subtle functional alteration is another possibility. In fact, functional impediment of INL has been reported in both conditions.…”
Section: Discussionmentioning
confidence: 99%